Energy efficiency as an instrument of regional development policy? The impact of regional fiscal autonomy. Issue 6 (3rd June 2019) - Figus, Gioele; Lecca, Patrizio; McGregor, Peter; Turner, Karen
ABSTRACT: This paper analyses the system-wide impact of increased household energy efficiency in a regional context, using Scotland as an example. It shows that household energy efficiency improvements typically deliver a 'double dividend' of a regional economic stimulus and reduction in energy use. However, the trade-off between the two is sensitive to the degree of regional fiscal autonomy, and so is likely to vary across regions. The use of taxation to support the implementation of energy-efficiency improvement programmes negatively impacts competitiveness, unless workers are willing to accept lower after-tax wages to fund public spending on improving household energy efficiency.